Linking Corporate Governance Mechanisms to Firm Performance: Evidence from Vietnam - Nga, Tran Thi; Binh, Vu Thi Thanh; Loan, Nguyen Thi Thanh (International Journal of Economics and Financial Issues, 2025)
Corporate governance plays a crucial role in enhancing firm performance by improving oversight and decision-making processes. This study examines the impact of corporate governance on financial performance with a control of earnings quality. Corporate governance includes ten proxies refecting characteristics of board of director (DoB), supervisory board, and risk management mechanism, while firm performance is measured by ROE. The study applies panel data analysis with a sample of 1,260 observations from non-financial listed companies in Vietnam from 2018 to 2023. The results indicate that BoD size positively affects ROE, while BoD duality and BoD meeting frequency have negative impacts. SB meeting frequency enhances financial performance, whereas supervisory board size and gender diversity exhibit negative effects on ROE. Outsourced internal audits significantly improve ROE, while the use of Big4 audit services does not show a statistically significant impact. Notably, earnings quality has a significantly positive influence on ROE, highlighting the importance of transparent financial reporting in enhancing financial performance. These findings provide empirical insights for policymakers and businesses to optimize governance structures. The study contributes to the corporate governance literature by offering evidence from an emerging market, emphasizing the role of boards and risk management mechanisms in enhancing financial performance.